Penguatan Implementasi Indonesian Good Agricultural Practices (IndoGAP) melalui Buku Log Budidaya Padi pada Kelompok Tani di Kabupaten Ngawi: Strengthening the Implementation of Indonesian Good Agricultural Practices (IndoGAP) through the Rice Cultivation Log Book in Farmer Groups in Ngawi Regency - Zidan Izzun Naja; Farikhah (Agrocentrum, 2026)
The implementation of Indonesian Good Agricultural Practices (IndoGAP) in rice farming is becoming increasingly important because it relates to product quality, traceability of cultivation processes, and opportunities to enhance the competitiveness of farmer groups. Challenges arise in the field when cultivation practices are not accompanied by proper record-keeping, making it difficult for groups to demonstrate their activity history and readiness for certification. This article aims to examine strategies for strengthening the implementation of IndoGAP through the development of a rice cultivation logbook for the Nglencong Sari III Farmers’ Group in Dempel Village, Geneng Subdistrict, Ngawi Regency. The study employed a descriptive qualitative approach using semi-structured interviews, field observations, and documentation conducted from October to December 2024. The study results indicate that the logbook, which follows the cultivation stages from planning through post-harvest and sanitation, can serve as a simple yet adequate recording tool for traceability. Its implementation tends to be more effective when started with core activities, accompanied by easy-to-understand examples of how to fill it out, driven by the group leader’s role, and reviewed periodically during group meetings. Thus, the cultivation logbook can serve as a practical instrument to strengthen the implementation of IndoGAP while organizing farm management to be more orderly, efficient, and market-oriented.